The Social Embeddedness of MSMEs Goyor Woven Sarong in Sambirembe Village, Kalijambe, Sragen - Arsita, Meita; Zuber, Ahmad; Demartoto, Argyo (Society, 2020)
Goyor woven sarong craft is one of the Micro, Small, and Medium Enterprises (MSMEs) in Wonosari Hamlet, Sambirembe Village, Kalijambe Sub-District, Sragen Regency, Central Java Province, Indonesia. The woven sarong craft is a cultural heritage passed down from generation to generation. The woven sarong craft business has survived even though the industrial-scale businesses have spread widely. In economic practice, economic actions among business actors of the woven sarong craft are based on cultural values. This research aims to analyze (1) the embeddedness of cultural values in economic practices of Goyor woven sarong; (2) the relational embeddedness between middlemen, collectors, and craftswomen; (3) the economic strategy of the Goyor woven sarong business. This research was qualitative research with a case study approach. The research analysis used the concept of economic actors’ embeddedness in the social networks approach by Granovetter. Research data was collected through in-depth interviews and direct observation. Informants were selected using a purposive sampling technique. The result shows that: 1) there is the embeddedness of cultural values on the woven sarong craft business sustainability. Woven sarong craft is a cultural heritage and work ethic has become the main foundation for business sustainability; 2) the relational embeddedness was manifested through mutual trust between the collectors, middlemen, and craftswomen through a sense of “ewuh pekewuh” (feeling bad, embarrassment, feeling uncomfortable), and through mutual need between the collectors, middlemen, and craftswomen; 3) the economic strategy of the Goyor woven sarong business actors follows the flow of community culture.